A DON’T IGNORE THE MENTAL HEALTH PROBLEMS OF POSTPARTUM MOTHERS - gultom, risatantry (Mitra Husada Health Internasional Conference (MIHHICo), 2024)
Background : Pregnant and postpartum women are more sensitive to mental health issues such as anxiety disorders, postpartum blues, stress, sleep problems, depression, and post-traumatic stress disorder (PTSD). This mental health issue is one of the consequences of the Covid-19 pandemic, which has affected modifications in hospital medical treatment. Purpose : Analyzing midwives' understanding of mental health problems in pregnant and postpartum women during. Method : This research design method is a mixed method (Mixed Method) using an Embedded Design approach. Quantitative data was collected using a Google form questionnaire, while qualitative data was gathered through in-depth interviews. In quantitative analysis, a design description is used, while in qualitative analysis, Nvivo 12 Plus is used. Results : Midwives have good knowledge as many as 13 people (76.5%) and sufficient knowledge as many as 4 people (23.5%). Based on the results of the interview, it said that the understanding of midwives still did not understand how to analyze the psychological status of mothers effectively because of the unavailability of special measuring tools for mental health problems and the lack of training to increase human resources for mental health problems for pregnant and postpartum women. Conclusion : The majority of midwives have good knowledge. Midwives' understanding reveals more about the factors that cause mental disorders from the incidence of pregnancy outside marriage and KTD. The IEC technique used by the midwife is able to analyze the mental health status of the mother and the obstacles experienced by the midwife, namely the lack of information support and instrumental support from the hospital. Keywords: mental disorders, pregnancy, postpartum, knowledge of midwives, understanding of midwives